Quality Using SERVQUAL to Enhance Customer Satisfaction and Loyalty at MSME Nyamilo - Gilang Permatasari, Trivena; Winda Purwaning Suhairiya; Sudarmiatin; Wening Patmi Rahayu (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to describe the service quality of Nyamilo MSMEs using the SERVQUAL model and to examine its relationship with customer satisfaction and loyalty. A qualitative approach was used through interviews with the owner and three customers who had made more than two purchases, accompanied by observations of online sales activities and documentation from social media. The results show that all five dimensions of SERVQUAL, namely tangibles, reliability, responsiveness, assurance, and empathy, are well fulfilled. Neat and hygienic packaging, consistent taste, quick response in communication, transparency in the production process, and the ability to customize orders are factors that shape a positive experience for customers. These findings indicate that good service increases satisfaction, which in turn encourages loyalty in the form of repeat purchases and recommendations to others. This study confirms that service quality plays a crucial role in retaining customers for online-based culinary SMEs like Nyamilo.